LES of a Low Velocity-Ratio Jet in a Flat-Plate Boundary Layer - Jewkes, James; Chung, Y. (Engineers Australia, 2010)
The Jet In Cross-Flow (JICF) is a commonly studied flow, particularly in the context of boundary layer control. A key parameter is the ratio between the mean velocity of the jet and the free-stream. Investigations have ranged from VR = 1:0 to VR = 10:0, however lower VR < 2:0 jets are poorly understood. Here, we present an LES model of a VR=1:0 perpendicular jet in a flat plate turbulent boundary layer.